Characteristics of Vulcanizate Rubber Using Composite Latex – Modified Cassava Starch as Filler - Hari Adi Prasetya; Popy Marlina; Arbi Dimyati (Indonesian Journal of Chemistry, 2018)
The research on Characteristic of vulcanizate rubber using cassava starch composite (Manihot glaziovii) modification - latex as filler has been done. The composite variation of cassava starch concentration is 0, 40, 80, 120, 160 and 200 phr in three replications. Microstructure and elemental samples in SEM EDX and FTIR Spectroscopy method analysis, while physical properties using the standard testing equipment. The results showed that the concentration of cassava has a significant influence that is hardness, tensile strength, elongation at break, tear resistance and ozone resistance. The best rubber hardness specification was composite with modified cassava starch concentrations of 120, 160 and 200 phr with value 57, 61 and 65 Shore A. The best tensile strength of cassava starch concentration 80 and 120 phr with value 160 and 167 kg/cm2, while the best result of the extension of cassava starch concentration elongation at break 80, 120, and 160 phr is 652, 741, and 748%, and tear resistance 80, 120, 160 and 200 phr with value 14.21, 15.96, 15.16 and 14.47. The ozone resistance for all concentrations meets the requirements of commercial vulcanizate rubber. The latex-modified cassava starch composite can be used as a filler for rubber products and as an alternative to commercial fillers.